Cytokine profile of gingival crevicular fluid in children with impaired immunological surveillance system - Iu. A. Kozlitina; O. I. Admakin; N. S. Morozova; N. B. Zakharova; O. L. Morozova (Сеченовский вестник)
Aim. To study the cytokine profile of the gingival crevicular fluid (GCF) in children with a juvenile rheumatoid arthritis (JRA).Materials and methods. We examined 20 children with JRA and 10 patients without somatic pathology aged 6 to 16 years old. The condition of periodontal tissues was assessed by periodontal indices – gingival index GI (Loe, Silness, 1963) and gingival bleeding index GBI. Biomaterial sampling from the gingival sulcus was carried out using special endodontic absorbent paper points. Enzyme immunoassay for IL-18, IL-10, IL-1ß, IL-1RA, MCP-1, VEGFs in the GCF was performed using the test kits of Vector-Best LLC (Novosibirsk, Russia).Results. Mean GI index in the JRA group was 0.31 ± 0.10 and in the control group – 0.20 ± 0.05 (p < 0.05), mean GBI index – 19.90 ± 3.14 and 10.80 ± 2.60 respectively (p < 0.05), which was accompanied by a more pronounced degree of inflammation of periodontal tissues. The GCF concentration of IL-18 in the JRA group was 6.70 (4.97–7.92) pg/ml, in the control group – 11.25 (8.70–13.10) pg/ml (p < 0.05), while the concentration of IL-1ß was 15.30 (13.79–17.18) pg/ml in the JRA group and 5.36 (5.32–5.54) pg/ml in the control group.The IL-10 concentration in the JRA group was 3.60 (2.89–4.45) pg/ml, which was comparable to the values of the control group. The concentration of IL-1RA was lower in the JRA group than in the control group: 3638.5 (2397.5–4133.5) pg/ml and 4951.0 (4303.0–5455.0) pg/ml respectively. The total GCF chemokine concentration for MCP-1 was determined at the level of 15.65 (14.15–17.39) pg/ml and 15.50 (12.80–21.20) pg/ml for the main and control groups and for VEGF – 49.60 (41.95–54.50) pg/ml in the JRA group and 12.00 (11.00–13.00) pg/ml in control group.Conclusion. In children with juvenile rheumatoid arthritis, an imbalance of pro- and anti-inflammatory cytokines in GCF plays a role in the development of gingivitis: an increased of IL-1ß concentration – a triggering factor of pro-inflammatory chains, a decreased concentration of IL-1RA – an anti-inflammatory cytokine, an increased concentration of VEGF – a marker of hypoxia.